Аdaptation of the principle of architectural design code for the coloristic organization of facades of residential areas on the example of Аlmaty - Almukasheva Д.Б.; Nazarova Д.А. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2025)
Active urbanization processes are increasingly influencing the architectural appearance of cities. The need to develop a comprehensive strategy for improving comfortable urban spaces arises from the low quality of life of the population and the unfavorable architectural appearance of cities. This highlights the importance of adopting one of the key strategic tasks at the present stage—the development of an architectural design code for all regions of Kazakhstan. Modern cities face numerous challenges in ensuring sustainable development, preserving cultural heritage, and creating a comfortable urban environment. Elements such as facades, recreational areas, small architectural forms, and advertising play a crucial role in shaping a cohesive city image. Thus, it is important to note that the architectural design code—a set of regulations governing the construction and development of the urban environment based on specific rules and standards—will become one of the key approaches to addressing these issues. This article will analyze the facades of residential areas in Almaty, providing an accurate basis for identifying further directions for urban development.